2019
DOI: 10.2355/isijinternational.isijint-2018-781
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Microstructures of Mo<sub>2</sub>C Strengthened Vanadis 4 Extra Alloy Steel by Powder Metallurgy and Heat Treatments

Abstract: In this work, different ratios of molybdenum carbide (1, 3 and 5 mass% Mo 2 C) powders were added to Vanadis 4 extra alloy steel powders and then mixed by ball milling for 6 h. The composite powders underwent vacuum sintering at 1 200, 1 220, 1 240, 1 260 and 1 280°C for 1 h, respectively. The results showed that the optimal sintering temperature for the addition of 5 mass% Mo 2 C powders was 1 220°C. It also represented that the apparent porosity was 0.18%, and that a transverse rupture strength (TRS) value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Generally speaking, the morphology and sizes of carbides are used to roughly judge the type of carbides. Besides, our previous study indicated that the identification of MC and M 6 C carbides can be carried out by a combination of EDS and XRD measurements [18]. In this work, EDS analysis results further confirmed that the refined carbides of the 1350°C-sintered Z1.8T1.2 specimen mainly belonged to V-rich MC carbides.…”
Section: Resultssupporting
confidence: 76%
“…Generally speaking, the morphology and sizes of carbides are used to roughly judge the type of carbides. Besides, our previous study indicated that the identification of MC and M 6 C carbides can be carried out by a combination of EDS and XRD measurements [18]. In this work, EDS analysis results further confirmed that the refined carbides of the 1350°C-sintered Z1.8T1.2 specimen mainly belonged to V-rich MC carbides.…”
Section: Resultssupporting
confidence: 76%
“…It can be improved the mechanical properties by using a series of heat treatments. Cryogenic treatment (also known as sub-zero), as an effective way to improve the properties of tool steels, since it enhances the transformation of retained austenite to martensite [15][16][17][18]. Therefore, we added Cr 3 C 2 -TaC-TiC carbides to Vanadis 23 powders as an innovative composite material, aimed to explore a series of vacuum sintering processes, sub-zero and heat treatments for Vanadis 23 composites, and further examined the effects on the sintering behaviour, strengthening mechanism, and mechanical properties of Cr 3 C 2 -TaC-TiC strengthened Vanadis 23 composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since the Mo 2 C carbides have refined particle size and uniform distribution, high-temperature strength of γ/NiMo alloys prepared by this dispersion strengthening process could be greatly improved [2]. Our previous study also showed that the hardness and strength values of the materials improved when the amount of Mo 2 C phase was increased [17]. As shown in Figure 2(b), where the crystal structure is gradually dominated by the hexagonal (Mo 2 C) structures as the sintering pressure increased.…”
Section: Resultsmentioning
confidence: 99%
“…A scanning speed of 0.01 v·s −1 , initial potential of −2.0 V, and the final potential of 2.0 V were controlled. The polarisation curve was obtained by Corr-View software to analyse and compare the corrosion potential ( E corr ), the corrosion resistance ( R corr ) and corrosion current ( I corr ) of the different sintering parameters [17]. Moreover, the voltage is V (volts) vs. SCE (saturated calomel electrode).…”
Section: Methodsmentioning
confidence: 99%